Rasionalisasi Jaringan Penakar Hujan Di Das Kedungsoko Kabupaten Nganjuk - Rodhita, Muhamad; Limantara, Lily Montarcih; Dermawan, Very (Fakultas Teknik, Universitas Brawijaya, 2012)
Kedungsoko River and its tributaries is located in Kediri and Nganjuk district. Kedungsoko river has approximate 416,54 km2 of watershed area number. Kedungsoko catchment area is affected by approximate 8 rain stations. There has not been studied theoretically about the optimum density and dispersal patterns of rainfall station networks that have been installed in the Kedungsoko watershed.Based on the results of assessment and analysis using Kagan-Rodda method, it was acquired 4 selected stations, while Kriging method obtained results of 8 selected stations that spreaded in Kedungsoko watershed. Relative error for design rainfall of Kagan-Rodda method is 1,906% and Kriging method is 2,802%. Relative error of hidrograf discharge unit for Kagan-Rodda is 38,53% and 19,83% for Kriging.Keywords: Rainfall station networks, Kagan-Rodda, Kriging